Penerapan Konsep Finite State Automata (FSA) pada Aplikasi Simulasi Vending Machine Yoghurt Walagri - Suharsih, Ririn; Atqiya, Firas (Jurnal Pendidikan Multimedia (Edsence), 2019)
Language theory and automata is a theory that related to abstract machines which in there is Finite State Automata. FSA can be implemented in design of a vending machine. Vending machines in Indonesia operate mostly with products such as canned drinks, plastic bottles, coffee, snacks, and tickets. This research discuss about simulating application design of Walagri Yoghurt vending machine, a yoghurt produced by Biotechnology Departement at the University of Muhammadiyah Bandung, based on the implementation of Finite State Automata. The conclusion obtained in this study is that Finite State Automata can be used as a basic logic for making vending machine simulations.